Morphohistological examination on somatic embryogenesis of Musa acuminata cv. Mas (AA) - Jalil, M.; Chee, W.W.; Othman, R.Y.; Khalid, N. (2008)
Somatic embryogenesis is a routine method in obtaining mass-production of plantlets especially in Musa spp. Somatic embryogenesis is a process characterized by a series of morphological changes leading to plant regeneration. Therefore it is important to identify stages in somatic embryogenesis through morphological and histological characteristics. In this study, stages of somatic embryogenesis through morphohistological study could differentiate between embryogenic callus consisting of somatic embryos and non-embryogenic callus. In Musa spp., globular to torpedo shaped somatic embryos resulted in good suspension cultures followed by recovery of somatic embryos during developmental stage. The morphological observations were supported by histological sections of structures at all particular stages. Histological examination also revealed the vascular connection in germinated somatic embryos which later turned into a complete plantlet.